If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7(k + -3) = 0 Reorder the terms: 7(-3 + k) = 0 (-3 * 7 + k * 7) = 0 (-21 + 7k) = 0 Solving -21 + 7k = 0 Solving for variable 'k'. Move all terms containing k to the left, all other terms to the right. Add '21' to each side of the equation. -21 + 21 + 7k = 0 + 21 Combine like terms: -21 + 21 = 0 0 + 7k = 0 + 21 7k = 0 + 21 Combine like terms: 0 + 21 = 21 7k = 21 Divide each side by '7'. k = 3 Simplifying k = 3
| 2a+3b+7c= | | 3x+54y-12=0 | | 6(3-4y)= | | n+29=48 | | -4(-2b-7)=-44 | | 1.84/2.85=5.14/t | | 3i*x=y | | 2(5t-4)+6=40-t | | 49.2=1.5h | | 2(4m+1)=3 | | 114/95=95/x | | 6.4=16y | | xx/7-3=4 | | (2x-7)3=10x-9 | | -43=x/16 | | x-1=6/x | | 6x^3+56=53x-x^2 | | 7=5/6b-8 | | Y^2+3y=x | | (6+4x)*(15x+25)=0 | | F(x)=4*logx | | 3485x^2-311107.5x-18855000=0 | | n/36=17/72 | | 7w+6-3w=6 | | 4(2b-5)=2b+10 | | X/5-7=2 | | 2.3=y+.9 | | 12c-48=84 | | 9x-5=3x+47 | | x(x+13)=40 | | (1+2i)*x+(3-5i)*y=1-3i | | -3=2-(-x/5) |